The Mediating Role of Work Satisfaction on the Effect of Organizational Justice on Employee Engagement - Haryono, Siswoyo (Advances in Social Sciences Research Journal, 2021)
This research evaluates the mediation role of job satisfaction on the effect of organizational justice on employee engagement among temporary employees at Universitas Muhammadiyah Yogyakarta. The population of temporary employees at Universitas Muhammadiyah Yogyakarta is 213, and the sample was 70. The analysis employed Smart PLS 3.0. The results show that organizational justice affects job satisfaction, and job satisfaction significantly affects employee engagement. Job satisfaction has a mediation role in the effect of organizational justice on employee engagement among temporary employees at Universitas Muhammadiyah Yogyakarta. The benefit of the research is that improving employee engagement would be adequate by increasing both job satisfaction and organizational justice.